Localization of the Adductor Tubercle in the Skeletally Immature: A Computed Tomography Study With Patellofemoral Surgical Implications. Issue 7 (June 2023) - Jabbouri, Sahir S.; McLaughlin, William; Joo, Peter; Cooperman, Daniel; Fulkerson, John P.; Frumberg, David B.
Background: The adductor tubercle of the distal femur is utilized by surgeons as an anatomic landmark to identify graft anchor placement during medial patellofemoral ligament (MPFL) and medial quadriceps tendon femoral ligament (MQTFL) reconstruction for patellofemoral instability. In the skeletally immature population, its location relative to the physis has not been well defined. Purpose: To identify the location of the adductor tubercle relative to the distal femoral physis in skeletally immature individuals and gain insight regarding optimal graft anchor placement for pediatric patients undergoing MPFL and MQTFL reconstruction. Study Design: Descriptive laboratory study. Methods: Thin-cut computed tomography scans of 37 male cadaveric specimens (age, 4-16 years) were obtained from the New Mexico Decedent Image Database. A measurement protocol to identify the adductor tubercle was created with guidance from a fellowship-trained musculoskeletal radiologist. By utilizing axial, coronal, and sagittal views of knee computed tomography scans, the adductor magnus tendon was identified and followed distally to its insertion (adductor tubercle) on the distal femur. Distance from the midpoint of the adductor magnus tendon insertion relative to the physis in the proximal-distal orientation was measured. The anterior-posterior distance of the midpoint tendon insertion relative to the posterior femoral cortex line was also evaluated. Results: The midpoint of the adductor magnus tendon was at the physis in 30 specimens. One 8-year-old cadaveric specimen had an insertion 1.1 mm distal to the physis. In all specimens ≥15 years old (n = 6), the adductor magnus tendon insertion was distal to the physis with a mean distance of 2.73 mm. The location of the adductor tubercle was always posterior (mean, 5.1 mm) with respect to the posterior femoral cortex line. Conclusion: The location of the adductor tubercle in male pediatric patients is likely at or distal to the physis. Thus, the findings of this study directly conflict with previous studies that suggested a more proximal location. Clinical Relevance: Optimal graft anchor placement during MPFL and MQTFL reconstruction in the skeletally immature patient can be challenging because of the variability reported in previous studies of the medial patellofemoral complex origin relative to the physis. This study suggests that distal—rather than proximal—graft anchor placement might better help restore patellofemoral isometry.